64.7k views
2 votes
Given f(x)=3x+12, what is f(f^-1(3))

User Dparpyani
by
5.7k points

1 Answer

5 votes

Answer:

3

Explanation:

We know:


f\bigg(f^(-1)(x)\bigg)=x

Therefore


f\bigg(f^(-1)(3)\bigg)=3

Other method.

Find
f^(-1)(x)


f(x)=3x+12\to y=3x+12

exchange x to y and vice versa:


x=3y+12

solve for y:


3y+12=x subtract 12 from both sides


3y=x-12 divide both sides by 3


y=(x-12)/(3)\to f^(-1)(x)=(x-12)/(3)


f\bigg(f^(-1)(x)\bigg) replace x in f(x) with the expression
(x-12)/(3)


f\bigg(f^(-1)(x)\bigg)=3\cdot(x-12)/(3)+12=x-12+12=x


f\bigg(f^(-1)(3)\bigg) - put x = 3 to
f\bigg(f^(-1)(x)\bigg)


f\bigg(f^(-1)(3)\bigg)=3

User Ponraj
by
5.7k points